Hubungan Umur dan Paritas Dengan Kejadian Abortus Di RSUD Kabupaten Rokan Hulu - Handayani, Eka Yuli (Jurnal Martenity and Neonatal, 2015)
Abortion is a threat or spending the products of conception before the fetus can live outside world or the fetus is less than 500 grams and less than 20 weeks gestation. In hospitals Rokan Hulu, there were 118 cases of abortion in 2013. The purpose of this study was to determine the relationship between age and parity with the incidence of abortion in the room midwifery in hospitals Rokan Hulu 2013. This study is analytic with cross sectional design. How to sampling by total sampling, data collection is done by using secondary data obtained from the register of medical record books Rokan Hulu General Hospital in 2013 as many as 172 people. Analysis of the data in this study treated bivariate (chi-square). The results of this research that the frequency distribution of maternal age and parity in hospitals Rokan Hulu on 122 people as much at risk age category (70.9%). The frequency distribution of abortion in hospitals Rokan Hulu as many as 118 (68.6%). Frequency distribution of maternal parity parity category 1 (primiparous) as many as 119 people (69.2%), and the minority on parity 2-4 (multiparous) for 6 persons (3.5%). Of the chisquarestatistical test result that there is a relationship between ageof pregnant women with abortion incidence in hospitals Rokan Hulu and there is a relationship between parity with the incidence of abortion in hospitals Rokan Hulu. It is recommended in pregnant women aged <20 years and> 35 years of employment as often as possible antenatal health terdekat.Dan mothers of children> 4 to space pregnancies.